National inception workshop: Myanmar: Agricultural transformation and market integration in the ASEAN region: Responding to food security and inclusiveness concerns - Southeast Asian Regional Center for Graduate Study and Research in Agriculture (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2017)
The Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA) and the Centre for Economic and Social Development (CESD), together with the International Food Policy Research Institute (IFPRI) and Myanmar’s Ministry of Agriculture, Livestock and Irrigation (MoALI), organized the national inception workshop of the project Agricultural Transformation and Market Integration in the ASEAN Region: Responding to Food Security and Inclusiveness Concerns on 30-31 March 2017. Experts from international organizations, government agencies, academic institutions, civil society and private sector representing Myanmar, the Philippines, Italy, India and the United States of America took part in the discourse on global, regional and national perspectives on agricultural transformation and market integration in the ASEAN region. The Myanmar National Inception Workshop had five objectives: (1) to gain good understanding of the structural transformation and market integration and implications for agricultural growth and food security in Myanmar, position/role of small farmers in ATMI and various initiatives to address food security and inclusiveness concerns in Myanmar; (2) to consult various stakeholders – ASEAN Member States (AMS), civil society organizations (CSOs)/farmers’ organizations (FOs), the private sector, and research institutions regarding the implementation of research project on ATMI; (3) to identify priority promising commodities for regional and global value chains; (4) to develop Country Action Plan towards the achievement of the project’s target outcomes: enhanced capacity of AMS to identify and design national strategies, policies, programs and national agri-food value chain investment initiatives that benefit small-scale rural producers (SSRPs); and (5) to initiate organization of the National Project Steering Committee (NPSC).